Modeling groundwater flow and salinity dynamics for developing polder management strategies in coastal Bangladesh - Mizan, Syed Adil; Jampani, Mahesh; Rahman, Md. A.; Hasib, Md. R.; Sena, Dipaka Ranjan; Mondal, M. K.; Alam, R.; Matheswaran, Karthikeyan (2024)
Coastal Bangladesh in the Ganges Delta is comprised of polders, which are unique hydrological boundaries that are crucial for the livelihoods of farmers and local dwellers. These polder systems are facing severe water scarcity for agricultural use in the dry season, and the shallow aquifer system is often saline because of sea level rise, tidal impacts, and incremental groundwater use during Rabi for irrigation. Integrated management options are needed for the polder systems to optimize the salinity conditions. In this context, a comprehensive groundwater flow and salinity transport model was developed for a polder near Khulna City in Bangladesh. Water and salinity dynamics were assessed to develop alternate polder management scenarios. The modeling framework involved coupling MODFLOW and SEAWAT models to evaluate salinity ingress to the aquifer due to tidal interactions and groundwater abstraction. The polder landscape in the Ganges delta system is aligned with a natural hydrological river boundary. The interplay between the polders and the surrounding river system is essential for maintaining the ecological balance of the delta. The controlled water levels within the polders support rice cultivation, aquaculture, and other agricultural activities, while the natural rainfall and tidal hydrology aid in replenishing the local aquifers. Aquifer parameters and geometry, water flows in the polder, climate, hydrology, and water quality data were collected from the field and also obtained from secondary sources. The model encompassed a detailed conceptualization of the polder aquifer system, including the dynamics of surface water-groundwater interactions with tidal intrusion induced salinity gradient. The calibrated model showed good agreement with observed or adopted and simulated groundwater levels within the polder. These findings highlight the significant influence of tidal dynamics in the peripheral rivers on seasonal variations in groundwater flow patterns and salinity dynamics. This model, with its robustness, can serve as a reliable tool for stakeholders and policymakers to design sustainable groundwater management strategies for the polder systems.